Respuesta :

Answer:

[tex]b=3[/tex]

Step-by-step explanation:

Given equation:

[tex]1+2b-13=12-4b-2b[/tex]

Solving for [tex]b[/tex]

Combining like terms on both sides.

[tex]2b+1−13=12-4b-2b[/tex]

[tex]2b-12=12-6b[/tex]

Adding [tex]6b[/tex] both sides to get [tex]b[/tex] terms on one side.

[tex]2b-12+6b=12-6b+6b[/tex]

[tex]8b-12=12[/tex]

Adding 12 both sides to isolate [tex]b[/tex] on one side.

[tex]8b-12+12=12+12[/tex]

[tex]8b=24[/tex]

Dividing both sides by 8.

[tex]\frac{8b}{8}=\frac{24}{8}[/tex]

∴ [tex]b=3[/tex]  (Answer)

Answer:

2b = 24 - 6b

8b = 24

b = 3